Radiological diagnostic methods in gastroenterology - Z. A. Lemeshko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To analyze the proceedings of the 22ndUnited Russian gastroenterological week devoted to radiological diagnostic methods in gastroenterology. Key points. Potential of radiological methods in diagnostics of the diseases of a gastrointestinal tract, hepatobiliary system, pancreas etc. are demonstrated. Radiological signs at chronic diffuse liver diseases, disorders of portal blood flow and associated extrahepatic hemodynamic disorders are present. Modern advances of elastometry at diseases of the liver, spleen and pancreas are reflected. Radiological features at medical emergencies with involvement of digestive organs (thrombosis, ileus, circulatory intestinal disorders, closed diaphragmatic trauma) are demonstrated. Conclusion. Presented data will provide general practitioners with expanded concept on diagnostic radiology potential in digestive diseases and indications for ultrasound procedures at primary diagnosis and in dynamic assessment - broad application of radiological tests in scientific research.